The Influence of Work Life Balance and Interpersonal Communication on Employee Performance PT. Bank Sumut KC Panyabungan - Lola Arriza Diara Nasution; Kartini Harahap (PT FORMOSA CENDEKIA GLOBAL, 2023)
Human resources are the most important asset owned by a company. Companies need human resources who have potential, loyalty and good performance for the company. The achievements of each employee are called performance. This research aims to determine the influence of work life balance and interpersonal communication on the performance of PT employees. Bank Sumut KC Panyabungan. The form of research is quantitative research with an associative approach. The analysis methods are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results of this research show that the work life balance variable and interpersonal communication variable have a partial and significant effect on employee performance, the work life balance variable and interpersonal communication variable also have a simultaneous and significant effect on employee performance.